COULTHARD, M. & CALDAS-COULTHARD, C. R. (EDS.) TEXTS AND PRACTICES. LONDRES: ROUTLEDGE, 1996, 294 PÁGS. - Gomes, Clarissa H. F. de Lima (Cadernos de Linguagem e Sociedade, 2010)
COULTHARD, M. & CALDAS-COULTHARD, C. R. (EDS.) TEXTS AND PRACTICES. LONDRES: ROUTLEDGE, 1996, 294 PÁGS.